Blood-brain barrier breakdown, neuroinflammation, and cognitive decline in older adults - Bowman, Gene L.; Dayon, Loïc; Kirkland, Richard; Wojcik, Jérôme; Peyratout, Gwendoline; Severin, India C.; Henry, Hugues; Oikonomidi, Aikaterini; Migliavacca, Eugenia; Bacher, Michael; Popp, Julius (Alzheimer's & dementia, 2018)
Blood-brain barrier (BBB) breakdown is observed in older versus younger adults and in late-onset Alzheimer's disease versus age-matched controls, but its causes and consequences in aging are unclear. We tested the hypothesis that BBB breakdown is associated with cognitive decline and inflammation in nondemented elders. Cerebrospinal fluid and serum inflammatory markers were measured using sandwich immunoassays in 120 subjects. Least Absolute Shrinkage and Selection Operator-logistic regression selected cerebrospinal fluid and serum signatures that best classified BBB impairment defined by the cerebrospinal fluid albumin index ≥9. Linear regression examined changes in Clinical Dementia Rating sum of boxes as a function of BBB integrity at baseline. Mean age was 70 years, mean Mini–Mental State Examination was 27, and BBB impairment was recorded in 13.5%. BBB breakdown was associated with cognitive decline (P = .015). Cerebrospinal fluid intercellular adhesion molecule-1, vascular endothelial growth factor, interleukin-8, serum amyloid A, macrophage derived chemokine, and gender generated an area under the curve of 0.95 for BBB impairment, and serum IL-16, VEGF-D, IL-15, and other variables generated an AUC of 0.92 for BBB impairment. BBB breakdown is associated with more rapid cognitive decline. Inflammatory mechanisms, including cell adhesion, neutrophil migration, lipid metabolism, and angiogenesis may be implicated.